Konsentrasiekampe vir swart vlugtelinge in die Heidelbergdistrik gedurende die Anglo-Boereoorlog - Pretorius, Willem; Pretorius, Fransjohan (Faculty of the Humanities, University of the Free State, 2011)
In the 1970s the phenomenon of black concentration camps in the Anglo-Boer War began receiving attention by historians. Despite the limited information available about the four black concentration camps in the Heidelberg district it is possible to form a picture of the experiences of the camp inhabitants, albeit with the assistance from official British documents – sources “from above”. Initially, the British authorities paid little attention to the black concentration camps. After the Native Refugee Department had taken over the control of the black concentration camps in June 1901, conditions improved. The establishment of black concentration camps was based on two principles, namely to ensure that sufficient labour was made available to the British army and to prevent black people from giving logistic or intelligence support to the Boer commandos. In the process the camps had to be self-sufficient. Large numbers of black men found employment in the army. On some of the deserted Boer farms blacks were agriculturally active, producing sufficient staple food for their own use. The poor health services in the black concentration camp at Heidelberg, where a high death rate occurred, improved to such an extent after June 1901 that there was a decrease in the number of deaths, making the death rate lower than that of the white concentration camp in the town.
Keywords: Concentration camps; Anglo-Boer War; Blacks; Heidelberg